KEMAMPUAN MENULIS TEKS ULASAN PESERTA DIDIK KELAS VIII SMP PANCASILA PAL IX KABUPATEN KUBU RAYA - Fadilah, Fadilah Dila; Heryana, Nanang; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
This study aims to determine the ability to write review texts for the short film